Islamic Education Service Marketing Management Based On Ismuba Identity As A Strategy To Strengthen Customer Loyalty In The Era Of Industrial Revolution 4.0 - Novia Nurhayati; Saipul Annur; Baharuddin Baharuddin (Jurnal Manajemen Pendidikan Islam Darussalam, 2026)
The era of the Industrial Revolution 4.0 demands that Islamic educational institutions effectively manage their service marketing strategies to remain competitive. This study aims to analyze the marketing management of Islamic educational services at SMA Muhammadiyah 2 Palembang using descriptive qualitative methods through interviews, observation, and documentation. This study analyzes how the ISMUBA identity is utilized in the marketing management of Islamic educational services as a competitive advantage for the school and its implications for building customer loyalty. The novelty of this research lies in viewing ISMUBA not merely as a unique Islamic curriculum, but as a religious branding instrument that strategically shapes the school's image, strengthens public trust, and encourages loyalty from parents and students. Thus, this study enriches the study of Islamic educational marketing by interpreting religious identity as a values-based marketing strategy